2022
DOI: 10.1186/s40945-022-00130-9
|View full text |Cite
|
Sign up to set email alerts
|

Can YouTube be used as an educational tool in lymphedema rehabilitation?

Abstract: Background Lymphedema is defined as the abnormal accumulation of interstitial fluid and fibro-adipose tissues resulting from injury, infection, or congenital abnormalities of the lymphatic system. The gold standard approach in the treatment of lymphedema is Complete Decongestive Therapy and it has many components that require practical knowledge and skills. YouTube can be a useful tool to provide these skills to healthcare professionals and patients. The aim of this study was to examine the vid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Following the removal of 3 878 duplicate studies, a total of 4 395 citations remained for title and abstract screening. A total of 26 studies were evaluated in full text review, yielding a total of 24 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 studies for final analysis.
Figure 1 Preferred reporting items for systematic reviews and meta-analyses (PRISMA) flow chart.
…”
Section: Resultsmentioning
confidence: 99%
“…Following the removal of 3 878 duplicate studies, a total of 4 395 citations remained for title and abstract screening. A total of 26 studies were evaluated in full text review, yielding a total of 24 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 studies for final analysis.
Figure 1 Preferred reporting items for systematic reviews and meta-analyses (PRISMA) flow chart.
…”
Section: Resultsmentioning
confidence: 99%
“…Unlike the other research, Springer et al 17 noted that medically trained individual videos, despite their higher content quality, received fewer likes. 14,31,32 This underscores the intricate nature of viewer preferences and engagement in medical and rehabilitation-related video content, necessitating further research for a comprehensive understanding of these dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…These deficiencies include inadequate reliability and content quality, a dearth of objectivity, and a lack of clarity and understandability in the presented information. [14][15][16][17][18] To the best of our knowledge, there exists no published study that specifically investigates the quality of CR-related videos available on YouTube. In the context of this study, our primary objective was to scrutinize and evaluate the reliability, accuracy, understandability, actionability, and popularity of CR videos hosted on YouTube, with a particular focus on their suitability as sources of information for patients in need of such content.…”
Section: What Are the Clinical And Research Implications?mentioning
confidence: 99%
“…Videos have been shown to significantly improve learning outcomes [13], however, mechanisms for controlling the content within online videos are limited. The results of internet searches are determined by an algorithm using likes, views, and popularity rather than an assessment of whether the content is suitable to guide skill acquisition [14,15] and previous studies have found online videos often omit key learning points and are of variable educational quality [14,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%